2018
DOI: 10.1136/bcr-2017-222326
|View full text |Cite
|
Sign up to set email alerts
|

A miraculous recovery:Bartonella henselaeinfection following a red ant bite

Abstract: The clinically important human infections are mostly caused by the three species (eg, ) of out of the many progressively increasing identified species. transmitted by the arthropod vector, fleas, after cat bite is responsible for the rare multisystem cat scratch disease in humans. We present an extremely rare case of contracted presumably through a red ant bite. The patient had a prolonged hospital stay for persistent encephalopathy due to delay in diagnosis and initiation of antimicrobial therapy. His hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In several case reports, however, B. henselae has been isolated in cats with a variety of clinical symptoms including endocarditis, seizure disorders, ocular disease, and hyperglobulinaemia [ 13 ]. B. henselae infection occurs in humans when the bacterium is accidently transmitted through the scratch or bite of a cat, but other modes of transmission such as red ant bites have been reported [ 14 ]. Flea infestation on domestic animal reservoirs such as cats and dogs are of rising concern, as resistance to flea control insecticides is increasing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In several case reports, however, B. henselae has been isolated in cats with a variety of clinical symptoms including endocarditis, seizure disorders, ocular disease, and hyperglobulinaemia [ 13 ]. B. henselae infection occurs in humans when the bacterium is accidently transmitted through the scratch or bite of a cat, but other modes of transmission such as red ant bites have been reported [ 14 ]. Flea infestation on domestic animal reservoirs such as cats and dogs are of rising concern, as resistance to flea control insecticides is increasing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…are zoonotic pathogens transmitted from mammals to humans through a variety of insect vectors including the sand fly, cat fleas, and human body louse [4,5]. New evidence suggests that ticks, red ants, and spiders can also transmit Bartonella [15,16,17,18]. Bed bugs have been implicated in the transmission cycle of B. quintana and have been artificially infected [19].…”
Section: Introductionmentioning
confidence: 99%
“…Research on potential arthropod vector species has shown varied results, as bacterial presence does not denote vector competency in transmitting the bacteria. However, aside from the vector-competent cat flea, documented cases of human infection have been associated with exposure to arthropods, including hard-bodied ticks [ 54 , 55 , 56 , 57 ], ants [ 58 ], and spiders [ 59 ]. Therefore, further investigation of potential vector species, as well as sources of vector infection, need to be addressed [ 60 ].…”
Section: Introductionmentioning
confidence: 99%